Radiofrequency Lesioning for Movement and Psychiatric Disorders-Experience of 107 Cases - Doshi, Paresh K. (Frontiers in Human Neuroscience, 2021)
Background Radiofrequency lesioning (RFL) though used since the 1950s, had been replaced by DBS in the ’90s. The availability of magnetic resonance-guided focused ultrasound for lesioning has renewed the interest in RFL. Objective This paper analysis RFL in contemporary Functional Neurosurgery for various indications and its outcome. Complication rates of RFL are compared with the same author’s experience of DBS. Methods: 107 patients underwent RFL between 1998-2019. Indications included Parkinson’s Disease (PD), tremors, dystonia, and obsessive-compulsive disorders (OCD). The surgeries performed include thalamotomy (29), pallidotomy (49), subthalamotomy (23), and anterior capsulotomy/nucleus accumbens lesioning (6). Appropriate rating scales were used for preoperative and postoperative evaluations. Results: There was a 25% recurrence rate of tremors for PD after thalamotomy. Writer’s cramp rating scale improved from a mean of 10.54 to 1.6 in task specific dystonia (TSD) patients, after thalamotomy. In PD patients, after pallidotomy, contralateral motor Unified Parkinson’s Disease Rating Scale (UPDRS) and dyskinesia scores, improved by 41% and 57%, respectively, at one-year. Burke-Fahn-Marsden Dystonia Rating Scale in hemidystonia patients improved from 18.04 to 6.91, at one-year. There was 32 and 31% improvement in total and motor UPDRS respectively in the subthalamotomy patients, at two-year. All patients of OCD were in remission. There were three deaths in the pallidotomy group. Postoperative, dysarthria, confusion, hemiparesis, dyskinesia, and paraesthesia occurred in 12 patients, of which, 7 were transient. Conclusion: RFL is a useful alternative in a select group of patients with tremors and dystonia. It is our preferred treatment option for TSD and OCD.